Immunologic responses to the major allergen of Olea europaea in local and systemic allergic rhinitis subjects. Issue 11 (15th October 2015) - Campo, P.; Villalba, M.; Barrionuevo, E.; Rondón, C.; Salas, M.; Galindo, L.; Rodríguez, M. J.; López‐Rodríguez, J. C.; Prieto‐del Prado, M. A.; Torres, M. J.; Blanca, M.; Mayorga, C.
Summary Objective To evaluate the in vivo and in vitro responses to nOle e 1 in allergic rhinitis (AR) and local allergic rhinitis (LAR) patients sensitized to olive tree pollen (OL) confirmed by nasal allergen provocation test (NAPT). Methods Twelve subjects with AR, 12 with LAR and 12 subjects as control group (CG) were selected. Skin testing and NAPT with nOle e 1 were performed. Eosinophilic cationic protein (ECP) and tryptase were measured in nasal lavages before and after NAPT. Serum IgE to OL allergens was measured by ELISA. Basophil activation tests (BAT) with OL and nOle e 1 and dendritic cell maturation/proliferation studies were carried out. Results All AR (12/12) and 10/12 (83%) of LAR had a +NAPT to nOle e 1. ECP levels in nasal lavages were significantly increased after NAPT in both AR and LAR compared with CG at 15 min (P < 0.05). Serum IgE was positive only in AR. All AR had +BAT responses to OL and 10/12 to nOle e 1 (83%); 8/12 LAR (66.6%) had a +BAT to OL and 4/12 (33%) to nOle e 1, with only one subject of the CG with a +BAT to both OL and nOle e 1 (8%). Dendritic cell proliferation to nOle e 1 was increased in AR compared to LAR and CG (P = 0.019 and P = 0.001, respectively). Conclusion Both AR and LAR had a similar in vivo response to nOle e 1 with release of inflammatory mediators. Specific basophil activation with OL and nOle e 1 was observed in LAR confirming previous data obtained with dust mites.